Effects of Roux-en-Y gastric bypass surgery on eating behaviour and allopregnanolone levels in obese women with polycystic ovary syndrome. (April 2015) - Turkmen, Sahruh; Andreen, Lotta; Cengiz, Yucel
Abstract Polycystic ovary syndrome (PCOS) is associated with abnormal eating habits. We examined whether surgical treatment affected allopregnanolone levels and eating behaviour in nine women with PCOS who qualified for Rou-en-Y gastric bypass surgery. Blood samples were obtained to measure sex-hormone-binding globulin, total testosterone, progesterone, and allopregnanolone, and eating behaviour was evaluated using the Three-Factor Eating Questionnaire before surgery and at 6 and 12 months after surgery. Body mass index and total testosterone levels decreased, and progesterone and sex-hormone-binding globulin levels increased after bariatric surgery compared with pre-surgical values. In patients with anovulatory menstrual cycles, both the serum allopregnanolone level and the allopregnanolone/progesterone ratio were unchanged after surgery. The patients had high uncontrolled and emotional eating scores, and low cognitive restraint scores before surgery, and these scores had improved significantly at 6 and 12 months after surgery. The presurgical allopregnanolone levels were significantly correlated with uncontrolled eating. In conclusion, these results suggest that allopregnanolone appear to be part of the mechanism underlying the abnormal eating behaviour of obese PCOS patients by causing the loss of control over food intake. Roux-en-Y gastric bypass surgery can improve eating behaviour and clinical symptoms, and may facilitate weight loss in obese women with PCOS.